20 years' experience with laparoscopic splenectomy. Single center outcomes of a cohort study of 500 cases. (April 2018) - Radkowiak, Dorota; Zychowicz, Anna; Lasek, Anna; Wysocki, Michał; Major, Piotr; Pędziwiatr, Michał; Budzyński, Piotr; Kulawik, Jan; Budzyński, Andrzej
Abstract: Background: Laparoscopic splenectomy (LS) has become the gold standard in elective spleen surgery. Although it is considered relatively safe, treatment results vary depending on a hospital's profile and the experience of the surgeon and center. We would like to present experience of a high-volume referral center with minimally invasive operations of the spleen. Material and methods: The retrospective cohort study included consecutive patients undergoing laparoscopic splenectomy in tertiary referral surgical center in 1998–2017. The entire study population (500 patients) was grouped into 5 cohorts of 100 consecutively operated patients. The primary endpoints were short-term outcomes of LS and secondary – analysis of indications and operative technique. The study group consisted of 316 women and 184 men, 46 (28–59) years old on average. Results: The most common indications for splenectomy were ITP (53%), lymphoma (21%) and spherocytosis (7%). Ratio of ITP versus other indications decreased significantly over time in favor of more difficult cases (<0.001). Average operative time of 100 (75–132.5) min and blood loss of 50 (20–150) ml were changing during study. Forty two patients required a blood transfusion with no difference among groups (p = 0.765). The use of postoperative drainage diminished from 100% to 7% (p < 0.001). The overall conversion rate (3%) and intraoperative complications (5%) did not differ among groups (p = 0.863 and 0.888). Perioperative morbidity was 8.6% and decreased significantly over time (OR: 0.78, 95%CI: 0.62–0.98). We noted mortality of 0.4% (1 patient in 1st and 1 in 5th group). Median LOS was 4 (1–16) days. A significant change in the operative technique from vessels first to hilar transection was noted. Conclusion: Laparoscopic splenectomy seems to be a safe method associated with a low risk of perioperative complications and mortality. A careful reproducible operative technique, along with a well-trained team and standardized modern postoperative care is critical to improving outcomes. Highlights: Laparoscopic splenectomy has low risk of perioperative complications and mortality. Outcomes depend on involvement of whole team in perioperative care. Modern postoperative care protocol is related to outcomes improvement. Careful reproducible operative technique is critical to improve outcomes.